Experimental and numerical research on high‐temperature thermal insulation performance of lightweight porous ceramic/nanomaterial composite structure. Issue 12 (17th December 2019) - Ren, H.Y.; Wu, D.F.; Wu, W.J.; Li, J.N.; Lin, L.J.
Abstract: The thermal protection structure of hypersonic vehicles must meet the design requirements of high efficiency and light weight, and its heating surface must also be able to withstand thermal erosion by high‐speed and high‐temperature airflow. In this paper, a light‐weight porous ceramic material and a lightweight nanoscale thermal insulation material with excellent thermal insulation performance are combined to form an integrated thermal protection structure. Experimental study and numerical simulation of the structure's high‐temperature thermal insulation performance are carried out. The experimental results show that a composite sheet made from a 20 mm‐thick lightweight porous ceramic material and a 10 mm‐thick nanomaterial exhibit a temperature drop of 85 % between its back surface and front surface in four thermal environments (1200, 1000, 800 and 600 °C) at 1800 s. This indicates excellent thermal insulation performance of the composite sheet. In addition, the operating temperature limit (<1000 °C) is obtained through high‐temperature thermal performance tests on single‐layer nanomaterial sheets and scanning electron microscopy results. This provides an important basis for determining and optimizing the thickness ratio of the two materials in composite structure.